If it's not what You are looking for type in the equation solver your own equation and let us solve it.
k-5=5+3k
We move all terms to the left:
k-5-(5+3k)=0
We add all the numbers together, and all the variables
k-(3k+5)-5=0
We get rid of parentheses
k-3k-5-5=0
We add all the numbers together, and all the variables
-2k-10=0
We move all terms containing k to the left, all other terms to the right
-2k=10
k=10/-2
k=-5
| (2x^2+5x-3)+(3x+7)=0 | | -8q=-6q-6 | | 0,7x2=70 | | -9g=7-10g | | 50=15+5c | | 6x=6+2 | | 90=7x-1-3x+2 | | d/7=0.9 | | 41/4x+31/2x=11 | | –9g=7−10g | | 6x=150° | | -9f=-7f-8 | | 17/4x+7/2x=11 | | 90=7x-1+3x-2 | | 6w-3=35 | | 2r^2+2r+4=0 | | -6k=-3k-9 | | -2=x^2-2x+5 | | a.8a-5=11 | | y=12(2-1)(2-2) | | i) 2X/3–3X/8=7/12 | | y=12(1-1)(1-2) | | 5m-25=95 | | 2x-5(2-2x)=5x-4 | | 5m–25=95 | | y=12(0-1)(0-2) | | f^2+13=157 | | 5+6z=(-11) | | 3y–7=56 | | 2a-14=4a+7 | | 2-|1/3q-7|=4 | | 73=9a-8 |